Validation of visual bacterial mat assessment at aquaculture sites through abiotic and biotic indicators - R. Knight (Elsevier, 2021)
Aquaculture conducted in sea cages typically releases organic and inorganic wastes which deposit at the seafloor and may influence resident benthic communities. In regions with predominantly hard bottom substrates such as Newfoundland, Canada, the monitoring of aquaculture waste buildup at the seafloor is conducted through the use of visual indicators such as bacterial mats. To ascertain the validity of bacterial mats as indicators of aquaculture deposits, we examine relationships between substrate elemental and organic matter concentrations, bacterial community composition and the presence or absence of white bacterial mats. Substrates with bacterial communities previously defined as belonging to high impact and recently disturbed bacterial clusters showed higher concentrations of abiotic markers of aquaculture compared to substrates with low impact or intermediate impact bacterial communities. Bacterial mat presence was associated with the four pre-defined bacterial community clusters, while mat absence was mainly observed in substrates with bacterial communities indicative of low impact. Although visual indicators are less sensitive ecological indicators of benthic aquaculture effects than the determination of the identity of bacterial communities, bacterial mat presence remains a valid indicator of aquaculture-linked deposits atop hard-bottom dominated substrates. However, the absence of bacterial mats may be indicative of conditions ranging from no aquaculture impacts to low levels of deposition, and should be interpreted with caution.